Biological effects of the olive tree and its derivatives on the skin. Issue 22 (25th October 2022) - Melguizo-Rodríguez, Lucía; González-Acedo, Anabel; Illescas-Montes, Rebeca; García-Recio, Enrique; Ramos-Torrecillas, Javier; Costela-Ruiz, Victor J.; García-Martínez, Olga
Abstract : The olive tree and its derivatives are of great interest in the field of biomedicine due to their numerous health properties. Abstract : The olive tree and its derivatives are of great interest in the field of biomedicine due to their numerous health properties. The aim of the present study was to identify the effects of the use of olive products, extra virgin olive oil (EVOO) and products derived from its extraction, on the skin. Numerous studies have pointed out the protective effect of olive compounds on skin ageing, thanks to their role in the different mechanisms involved in the ageing process, such as reducing oxidative stress, increasing cell viability and decreasing histological alterations. With regard to their photoprotective effect, the olive tree and its fruit contain phenolic compounds which have a protective effect against radiation, such as low ultraviolet absorption and high antioxidant activity, acting as a protective factor against photocarcinogenesis. Similarly, the anti-tumour effects of olives have been studied at the level of the different compounds and extracts obtained from them, and their ability to selectively attack human melanoma cells has been observed. They have also shown antibacterial activity against microorganisms particularly implicated in skin infections, such as Escherichia coli, Candida albicans, Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Pseudomonas aeruginosa and Proteus spp. Likewise, on healthy tissue, they have shown the ability to stimulate growth, migration and the expression of genes involved in cell differentiation, which favours the regeneration of skin wounds. According to the results included in this review, the olive tree and its derivatives could be useful in the treatment of many skin conditions.